On‐Chip Electrical Monitoring of Real‐Time "Soft" and "Hard" Protein Corona Formation on Carbon Nanoparticles (Small Methods 7/2020). Issue 7 (6th July 2020) - Srivastava, Indrajit; Khan, Muhammad S.; Dighe, Ketan; Alafeef, Maha; Wang, Zhen; Banerjee, Tuseeta; Ghonge, Tanmay; Grove, Lauren M.; Bashir, Rashid; Pan, Dipanjan
Abstract : In article number 2000099 by Dipanjan Pan and co‐workers, an integrated microfluidic platform coupled, with an electrical resistance measurement setup aided with a wavelet transform and machine learning algorithms, is developed to monitor the real‐time formation of protein corona and discrimination of their fouling behavior based on nanoscale surface chemistries.